Interpersonal Psychotherapy (IPT) for PTSD: A Case Study. - RAFAELI, ALEXANDRA KLEIN; MARKOWITZ, JOHN C. (American Journal of Psychotherapy (Association for the Advancement of Psychotherapy), 2011)
Interpersonal Psychotherapy (IPT), a time-limited, evidence-based treatment, has shown efficacy in treating major depressive disorder and other psychiatric conditions. Interpersonal Psychotherapy focuses on the patient's current life events and social and interpersonal functioning for understanding and treating symptoms. This case report demonstrates the novel use of IPT as treatment for posttraumatic stress disorder (PTSD). Preliminary evidence suggests IPT may relieve PTSD symptoms without focusing on exposure to trauma reminders. Thus IPT may offer an alternative for patients who refuse (or do not respond to) exposure-based approaches. Interpersonal Psychotherapy focuses on two problem areas that specifically affect patients with PTSD: interpersonal difficulties and affect dysregulation. This case report describes a pilot participant from a study comparing 14 weekly sessions of IPT to treatment with two other psychotherapies. We describe the session-by-session IPT protocol, illustrating how to formulate the case, help the patient identify and address problematic affects and interpersonal functioning, and to monitor treatment response.